Inside Cover: A V‐Shaped Polyaromatic Amphiphile: Solubilization of Various Nanocarbons in Water and Enhanced Photostability (Chem. Eur. J. 36/2015). Issue 36 (25th August 2015) - Kondo, Kei; Akita, Munetaka; Nakagawa, Takafumi; Matsuo, Yutaka; Yoshizawa, Michito
<x xml:space="preserve">Abstract</x> A new protocol for solubilizing various nanocarbons such as spherical fullerenes Cn (e.g., n=60, 70, and 84), planar polyarenes (e.g., tetracene, coronene, and hexabenzocoronene), and cylindrical carbon nanotubes (e.g., SWCNTs and MWCNTs) in water through manual grinding with V‐shaped polyaromatic amphiphiles is described in the Full Paper by K. Kondo and M. Yoshizawa et al. on page 12741 ff. The obtained aqueous nanocomposites are composed of nanocarbons encircled by the polyaromatic panels of the amphiphiles through multiple aromatic–aromatic interactions. Notably, the encapsulated photosensitive nanocarbons, such as tetracene and fullerene dimer C120 , exhibit high stability toward light.